2016
DOI: 10.18632/oncotarget.13568
|View full text |Cite
|
Sign up to set email alerts
|

Activation of chronic toxoplasmosis by transportation stress in a mouse model

Abstract: Toxoplasma gondiiis an obligate intracellular parasite infecting 25% of the world population and enormous number of animals. It can exist in two forms in intermediate hosts: the fast replicating tachyzoites responsible for acute infection and the slowly replicating bradyzoites responsible for life-long chronic infection. The interconversion between tachyzoites and bradyzoites plays critical roles in the transmission and pathogenesis of T. gondii. However, the molecular mechanisms that govern the interconversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In addition, IFN‐γ and IL‐6 have been implicated as major factors causing a number of neurological disorders which stems from dysregulation of several metabolic pathways incurred by inflammatory responses 26‐28 . The overproductions of pro‐inflammatory cytokines such as IFN‐γ and IL‐6 by T gondii ME49 infection contributes to inflammatory diseases 29‐31 . Therefore, to determine whether VLP immunization effectively inhibited the inflammatory response in the brain, IFN‐γ and IL‐6 expression levels were quantified.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IFN‐γ and IL‐6 have been implicated as major factors causing a number of neurological disorders which stems from dysregulation of several metabolic pathways incurred by inflammatory responses 26‐28 . The overproductions of pro‐inflammatory cytokines such as IFN‐γ and IL‐6 by T gondii ME49 infection contributes to inflammatory diseases 29‐31 . Therefore, to determine whether VLP immunization effectively inhibited the inflammatory response in the brain, IFN‐γ and IL‐6 expression levels were quantified.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have no way to determine whether any of the subjects had either been exposed to the infection more than once or whether an existing infection had been reactivated at some point. Recent animal studies have demonstrated that situational factors such as stressors can reactivate a chronic T. gondii infection with conversion of T. gondii bradyzoites to tachyzoites (Shen, et al, 2016). In animals, an increase in tachyzoites in chronic T. gondii infection is associated with increases in IgG and IgA but not IgM antibodies (Singh, et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…On the basic research side, although so far the contribution from Chinese scientists to the understanding of biology, as well as mechanisms of pathogenesis of T. gondii is limited, it is obvious that the research activities are really booming after the year 2000. Currently, there are groups working on the host mechanisms that restrict parasite infections (Qin et al, 2017 ), parasite mechanisms of immune evasion (Xue et al, 2017 ), molecular basis for T. gondii invasion (Wang Y. et al, 2014 ; Wang M. et al, 2017 ), growth and differentiation (Shen et al, 2016 ), etc. Besides these common research interests shared by the whole community, studies addressing the population structure of strains prevalent in China, the unique biological properties of ToxoDB #9 strains, and interplays between local prevalent strains and animal hosts are also required.…”
Section: Conclusion and Perspectivementioning
confidence: 99%